Theoretical aspects of national competitiveness in a globalization conditions . (Journal of Economic Research & Business Administration, 2015)
Qualitative changes, associated with the development of innovation and technological progress in the world economy in the context of globalization, sharpen competition between countries, regions, enterprises, contributing to the fact that producers’ competitiveness becomes a force of the state. This article deals with theoretical aspects of national competitiveness in a globalizing world. The authors reveal the criteria, sources and factors that determine the essence of competition and competitiveness in general. The theory and views of domestic and foreign scientists are presented and analyzed, as well as the author’s approach to the defi nition of national competitiveness. Accordingly, the national competitiveness, in our opinion, is the ability of the economy to provide the country with high rates of economic growth achieved through the application of innovative technologies, while making effi cient use of the limited resources , quality education and social and industrial infrastructure, depending on the direction of the country . The authors examined the substance of each level of competitiveness and the factors contributing to increase of competitiveness of the region, businesses , products, their relationship . The main and key elements, that determine the competitiveness of enterprises, and a criteria for evaluating the global competitiveness index , the place and role of Kazakhstan in it are analyzed.
Keywords: national competitiveness; regional competitiveness; enterprise competitiveness; product competitiveness; innovation; economic growth